Fish Consumption in the State of São Paulo – main species consumed and consumer socioeconomic profile (Research, Society and Development, 2024)
A diet that includes frequent and varied fish and seafood can reduce the risk of cardiovascular diseases and helps with neurological development and mental issues. In this context, it is important to obtain answers regarding the factors associated with consumption, but also the factors that can lead to an increase in fish consumption in certain regions and the obstacles that can be faced to solve these difficulties. Objective: This research assessed the profile of fish and seafood consumption and consumers in the State of São Paulo, as well as determining the main fish species consumed. Methods: This market study was carried out using an online questionnaire on fish consumption consisting of 23 questions, including a Free and Informed Consent Form agreeing to participate in the research. Results: 1,947 responses were obtained for the market study on fish consumption in the State of São Paulo. Of the volunteers who responded to the online questionnaire, 62% were female, with the predominant age group being 40 to 59 years old (43%). The species indicated as the most consumed were tilapia, salmon, hake, tuna, sardines, dogfish, cod and shrimp. Conclusion: This survey indicates that in the State of São Paulo there is low consumption and low frequency of fish consumption. The most purchased form of preservation was frozen fish in the form of fillets, with price still being a limiting factor for consumption.